2021
DOI: 10.1016/j.ssmph.2021.100743
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of workplace health promotion programs on self-perceived health of employees with a low socioeconomic position: An individual participant data meta-analysis

Abstract: The aim of the current study was to evaluate whether workplace health promotion programs improve self-perceived health of employees with a low socioeconomic position (SEP), and whether differential effects exist between individuals with a low SEP for gender, marital status or age. Individual participant data from six Dutch intervention studies aiming at promoting healthy behavior and preventing obesity in the work setting, with a total of 1906 participants, were used. The overall intervention effect and intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…An unique future of this study was the active role employees played in defining the central themes of the intervention. Participatory research designs are not yet common in the field of WHP, although they have been recommended [ 11 , 32 , 33 ] and explored [ 34 , 35 ]. In a classification of the degree of participation in participatory research from Fetterman [ 36 ], this study could be classified in ‘Collaborative Evaluation’.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An unique future of this study was the active role employees played in defining the central themes of the intervention. Participatory research designs are not yet common in the field of WHP, although they have been recommended [ 11 , 32 , 33 ] and explored [ 34 , 35 ]. In a classification of the degree of participation in participatory research from Fetterman [ 36 ], this study could be classified in ‘Collaborative Evaluation’.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is doubtful if WHP in its current form does contribute to the reduction of health inequalities. Recent Individual Participant Data (IPD) meta-analyses on in total 15 Dutch WHP intervention studies, showed no effects on BMI [ 9 ]—except from small effects for high-risk groups under specific conditions—and no effects on lifestyle behaviors [ 10 ] of employees with both low and high SEP, and no effects on self-perceived health of employees with a low SEP [ 11 ]. A meta-analysis including mainly intervention studies from the US found some evidence that physical activity interventions at work may be effective in reducing health inequalities, but the evidence base was small and of low quality [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the findings are applicable for high SES individuals. More and carefully designed research is needed for lower SES populations (Côté et al , 2020; van Heijster et al , 2021) who may even profit more from WHP interventions (van de Ven et al , 2020; van der Put et al , 2020), but require more encouragement to participate (van der Put et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There are various individual factors that can influence participation in health-promotion offers, e.g., self-rated health or perceived risk of an illness [31,51], together with socioeconomic aspects (education, poverty [52][53][54]). As described above, the study covers perceived need for the offer, interest, and whether the offer did (not) fit the needs.…”
Section: Limitations Of the Studiesmentioning
confidence: 99%